Role of Intraoperative Scrape Cytology in Diagnosis of Palpable Breast Lump (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background: Diseases of the breast constitute a significant proportion of surgical cases and frequently, the need arises to distinguish benign from malignant lesions prior to definitive treatment. So far, Frozen Section (FS) is the standard technique with high level of validity. However, intraoperative scrape cytology can be adopted when special facilities of FS are not available.Methods: This study designed with the aim to evaluate the value of Intraoperative Scrape Cytology (IOSC) in providing rapid and accurate diagnosis for breast lump and to compare its diagnostic yield with that of paraffin sections. This cross sectional descriptive study was carried out in the Department of Pathology, Chittagong Medical College in collaboration with Department of Surgery of this institution from October 2013 to September 2014. The study conducted on 123 patients with breast lumps who underwent operative treatment. Scrapings were taken from each specimen before formalin fixation and stained by rapid Papanicolaou staining. In each case their accuracy was compared to histopathological diagnosis. Statistical analysis done employing c2 test.Results: Out of 123 cases studied, 122 could be correctly differentiated into benign and malignant tumors with an accuracy rate of 99.19%.Conclusion: Intraoperative Scrape Cytology (IOSC) is a simple, accurate, rapid and cost-effective diagnostic tool, not requiring specific instruments in contrast to frozen section, can be used peroperatively for both diagnosis and management of breast lump.Chatt Maa Shi Hosp Med Coll J; Vol.17 (2); Jul 2018; Page 26-30